1998
DOI: 10.1097/00005768-199802000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Familial resemblance for ??VO2max in the sedentary state: the HERITAGE family study

Abstract: This study investigates the familial resemblance of maximal oxygen uptake (VO2max) based on data from 86 nuclear families of Caucasian descent participating in the HERITAGE Family Study. In the current study, VO2max was measured twice on a cycle ergometer in 429 sedentary individuals (170 parents and 259 of their offspring), aged between 16 and 65 yr. The VO2max was adjusted by regression procedures for the effects of 1) age and sex; 2) age, sex, and body mass; and 3) age, sex, body mass, fat mass, and fat-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
278
1
8

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 428 publications
(302 citation statements)
references
References 15 publications
15
278
1
8
Order By: Relevance
“…A tremendous amount of research has considered the modifying role of environmental factors on maximal aerobic exercise (e.g., training). It is well accepted that the variation seen in human maximal exercise endurance is due to the influence of genetic factors (3), and current estimations of the contribution of genetics to maximal exercise endurance range from Ϸ51% in humans (3) to 58 -90% in mice (23,26) to 39% in rats (18). However, the specific genes that determine an individual's maximal exercise endurance have not been identified.…”
mentioning
confidence: 99%
“…A tremendous amount of research has considered the modifying role of environmental factors on maximal aerobic exercise (e.g., training). It is well accepted that the variation seen in human maximal exercise endurance is due to the influence of genetic factors (3), and current estimations of the contribution of genetics to maximal exercise endurance range from Ϸ51% in humans (3) to 58 -90% in mice (23,26) to 39% in rats (18). However, the specific genes that determine an individual's maximal exercise endurance have not been identified.…”
mentioning
confidence: 99%
“…For example, the genetic substrate of exercise capacity includes genes that determine the intrinsic exercise capacity of the untrained individual as well as genes that are responsible for regulating the adaptive responses to regular physical activity (9,11,12). It has been estimated that genes determining the intrinsic exercise capacity of the untrained individual account for up to 50% of the variations in individual exercise capacity (10). Previous studies comparing sedentary and exercisetrained animals have been unable to determine the relative contribution of genetic (intrinsic) and environmental (training status) influences mediating the mechanisms of arrhythmia suppression by regular physical activity.…”
mentioning
confidence: 99%
“…It has been reported that genetic factors account for a significant proportion of variability in exercise-related phenotypes, such as maximal oxygen uptake (VO 2 max ) and exercise blood pressure, both in the sedentary state and in response to endurance training (2,(4)(5)(6). Identification of the genes and mutations responsible for these genetic effects would lead to a better understanding of the biology of adaptation to exercise and, ultimately, enable individualized prescription of exercise training for performance enhancement and for prevention and treatment of several public health problems.…”
mentioning
confidence: 99%